2007
DOI: 10.1002/dvg.20262
|View full text |Cite
|
Sign up to set email alerts
|

An allelic series for studying the mouse Thoc1 gene

Abstract: Thoc1 encodes an essential component of the mammalian TREX protein complex. TREX is an evolutionary conserved complex that couples elongating RNA polymerase II with RNA processing factors. Depletion of Thoc1 protein (pThoc1) compromises transcriptional elongation and nuclear export of some RNAs. Loss of Thoc1 causes periimplantation embryonic lethality in the mouse. Early embryonic lethality precludes analysis of the physiological requirements for Thoc1 in the developing embryo or adult. To circumvent this lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 24 publications
1
26
0
Order By: Relevance
“…Inducible Cre recombinase-mediated Thoc5 gene deletion has been reported to affect hematopoiesis, but effects on other tissues are unknown because of the limited distribution of tissues suffering Thoc5 deficiency (20). Mice homozygous for a hypomorphic Thoc1 allele, which expresses reduced Thoc1 protein in many tissues, are viable but sterile (19,25). This supports the hypothesis that different tissues have different requirements for Thoc1 during development.…”
supporting
confidence: 53%
“…Inducible Cre recombinase-mediated Thoc5 gene deletion has been reported to affect hematopoiesis, but effects on other tissues are unknown because of the limited distribution of tissues suffering Thoc5 deficiency (20). Mice homozygous for a hypomorphic Thoc1 allele, which expresses reduced Thoc1 protein in many tissues, are viable but sterile (19,25). This supports the hypothesis that different tissues have different requirements for Thoc1 during development.…”
supporting
confidence: 53%
“…We have recently generated a conditionally excisable allele of the murine Thoc1 gene that facilitates stable depletion of pThoc1 (26). The modified Thoc1 allele (Thoc1F) contains lox P sites within introns 5 and 7.…”
Section: Resultsmentioning
confidence: 99%
“…Murine embryonic fibroblast (MEF) cultures were isolated from F/Ă€ and F/+ littermate embryos at 13.5 days of gestation by standard procedures. The construction and genotyping of the floxed Thoc1 allele has previously been described (26). Cells were cultured in DMEM supplemented with 10% fetal bovine serum, 2 mmol/L L-glutamine, and 0.5% penicillin and streptomycin and grown at 37jC in a humidified atmosphere of 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a role for mouse Thoc1/ Hpr1/p84 during embryogenesis was revealed using mice containing the mutant alleles (Wang et al 2006(Wang et al , 2007, and researchers have now started to analyze THO components in a physiological context in multicellular organisms. In the present study we showed that mutations in EMU and AtTHO2 compromise Arabidopsis development.…”
Section: Discussionmentioning
confidence: 99%